The emerging roles of N6-methyladenosine RNA methylation in human cancers - Huafei Shen; Yifen Lan; Yanchun Zhao; Yuanfei Shi; Jie Jin; Wanzhuo Xie (BMC, 2020)
Abstract N6-methyladenosine (m6A) is the most abundant form of mRNA modification in eukaryotes. It affects various aspects of RNA metabolism, including nuclear export, translation, decay and alternative splicing. In addition, m6A also participates in a great number of human physiological processes, ranging from spermatogenesis modulation, response to heat shock, the control of T cell homeostasis to stem cell proliferation and differentiation. The dynamic equilibrium of m6A level is regulated by m6A methyltransferases ("writers"), m6A demethylases ("erasers") as well as m6A-binding proteins ("readers"). Once the balance is broken, numerous diseases will knock on the door. Recently, increasing studies reveal that m6A methylation exerts a profound impact on tumorigenesis and tumor progression. Therefore, in this review, we summarize the functions of m6A modification and its emerging roles in human cancers, and discuss the potential of m6A regulators as biomarkers or therapeutic targets.